Gestão ambiental e competitividade no setor da construção civil :um estudo sobre a aceitabilidade de práticas ambientais no mercado imobiliário - Silva, Raimundo Moisés Leite e (2006)
This work investigates the importance of Eco-Materiais applied in the civil construction and the necessity of knowledge of the real estate market, showing the importance of application of recycled products where inserted inside of a bigger scope of the sustainable development which has the subjects as the ambient management. In the theoretical referencial boarded the recycled and perfectly ecological products that demonstrate the applicability of this type of products in the sector of the civil construction, beyond the economic and social placesThe main popouse of the real estate sector is to show the awareness and demonstration in the negotiation of property constructed with these products, therefore, already it is practised by the market of the civil construction where much time sao commercialized by real estate and the its correctors lacking in same knowledge that is more deepened on these materials, having this evidence been made with statistical application of questionnaire and analyzed with base. We finish showing the statistical results with application of 142 questionnaires in a universe of 145 real estate from Natal/RN. With this, we may say that today exists a very strong concern with the environmental laws and the generated ambient impact in the civil construction and that the real estate sector has a feeling that the necessity of if inserting in this process, therefore, the real estate market in our State is in expansion and sensible to the necessity of changes, since the Natal/RN meets in the script of the tourism the International demanding of the professional that a globalized knowledge works with property, so the necessity of understanding the environmental laws and understanding application of the echo-materias used in the construction will give a better quality of life and at the same time to protect the nature